The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3906/biy-1502-51
|View full text |Cite
|
Sign up to set email alerts
|

Tracking coformulated strains of the entomopathogenic fungi Beauveria bassianaand Metarhizium anisopliae using SCAR markers

Abstract: This article examines the development of strain-specific sequence-characterized amplified region (SCAR) molecular markers in two strains of Beauveria bassiana and Metarhizium anisopliae, as well as their use for tracking pathogens in coinfected insect pests. The markers were designed based on the polymorphic introns of the large subunit region of the ribosomal DNA. These markers were used to distinguish between two strains of Beauveria (B55 and B51) and two strains of Metarhizium (M20 and M48). The entomopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…). Lower dose can cause even highly competitive genotypes to lose their advantage (Ben‐Ami & Routtu ; Ummidi & Vadlamani ), possibly because they are more easily overcome by the immune system or competitors when in small numbers. Testing our model for a wide range of parameter values revealed that the predictions are robust to different allogrooming efficiencies (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…). Lower dose can cause even highly competitive genotypes to lose their advantage (Ben‐Ami & Routtu ; Ummidi & Vadlamani ), possibly because they are more easily overcome by the immune system or competitors when in small numbers. Testing our model for a wide range of parameter values revealed that the predictions are robust to different allogrooming efficiencies (Fig.…”
Section: Discussionmentioning
confidence: 99%